Health education : a new approach - Ramachandran, L.; Dharmalingam.T (New Delhi : Vikas Publishing House Pvt. Ltd, 2022)
Considered the best overall introduction to the growing field of health education and promotion, the text connects fundamental topics to research, resources, and practitioners. It covers the roles and responsibilities of health education specialists, potential occupational settings, and the ethics that inform professional decisions. Looking at the past, present, and future of health, health care, and health education and promotion, the book features discussions of recent health reforms, the evolving professional landscape, the use of social media in health promotion, and much more.
Includes index.
Keywords: Education; Health education